Remembering a Dream: The Tragedy of Romantic Memory in the Modulatory Processes of Schubert's Sonata Forms - Black, Brian (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2005)
The idea of the dream as a longed-for alternative to reality imbues many of Schubert's finest sonata forms with what Charles Rosen has isolated as the tragedy of Romantic memory, the yearning for "that which never was." Here the unusual methods Schubert uses to modulate in his transitions create a sense of something alluring, yet insubstantial, in the subordinate key/theme, an effect that is maintained across the movement, whose progress thus ultimately suggests the tragic pursuit of an illusion.